2015
DOI: 10.1038/ncomms7806
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hall resistance standards from graphene grown by chemical vapour deposition on silicon carbide

Abstract: Replacing GaAs by graphene to realize more practical quantum Hall resistance standards (QHRS), accurate to within 10−9 in relative value, but operating at lower magnetic fields than 10 T, is an ongoing goal in metrology. To date, the required accuracy has been reported, only few times, in graphene grown on SiC by Si sublimation, under higher magnetic fields. Here, we report on a graphene device grown by chemical vapour deposition on SiC, which demonstrates such accuracies of the Hall resistance from 10 T up to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 52 publications
3
76
1
Order By: Relevance
“…The quantum Hall plateaus observed in graphene on SiC (G/SiC) have a high breakdown current [4] and appear at lower magnetic fields [5] with respect to graphene deposited on SiO 2 [6]. The quantum plateaus in G/SiC devices are much larger in magnetic field than those obtained in graphene encapsulated in hBN [7], because they are stabilized by charge transfer [8] and disorder [9]. Thanks to these properties, it was recently demonstrated that G/SiC can act as a quantum electrical resistance standard [10], even in experimental conditions relaxed with respect to the state of the art in GaAs-based quantum wells [11].…”
Section: Introductionmentioning
confidence: 98%
“…The quantum Hall plateaus observed in graphene on SiC (G/SiC) have a high breakdown current [4] and appear at lower magnetic fields [5] with respect to graphene deposited on SiO 2 [6]. The quantum plateaus in G/SiC devices are much larger in magnetic field than those obtained in graphene encapsulated in hBN [7], because they are stabilized by charge transfer [8] and disorder [9]. Thanks to these properties, it was recently demonstrated that G/SiC can act as a quantum electrical resistance standard [10], even in experimental conditions relaxed with respect to the state of the art in GaAs-based quantum wells [11].…”
Section: Introductionmentioning
confidence: 98%
“…The most widely studied among the carbon sources is propane [114,121,124,126,[128][129][130][131][132][133][134][135][136][137]. There is only a few works devoted to ethene [125], toluene [127] and xylene [127] as carbon sources for graphene growth on silicon carbide.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%
“…There is a lot of excellent reports in literature dealing with deposition of graphene from external sources on metallic surfaces (Cu, Ni, Ir, etc) and on dielectric wafers (SiC, sapphire, Si, etc.). Following the main purpose of this review paper, we focus only on the CVD and MBE growth of graphene on silicon carbide [114,121,[123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141]. Therefore, the aim of this subsection is twofold: (i) to understand the main difference between thermal decomposition of silicon carbide and bottom-up growth of graphene on SiC and (ii) to extensively review the literature concerning the CVD and MBE growth processes with participation of SiC substrate.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%
“…Various works have proved the universality and reproducibility of quantum Hall resistance standard metrology in graphene with accuracy as high as part-per-billion [20][21][22][23][24]. Quantum resistance devices based on graphene have been realized on graphene grown on silicon carbide wafer [20][21][22][23][24][25][26]. More importantly, QH effect can be realized in graphene at room temperature [27], which makes graphene-based QH device a very attractive choice of a practical resistance definition for routine calibration, and a potential alternative to replace GaAs based device in the SI unit definition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the metrology of resistance standard, including a practical (non-SI) definition for increasing potential end users, is getting more and more important. Various works have proved the universality and reproducibility of quantum Hall resistance standard metrology in graphene with accuracy as high as part-per-billion [20][21][22][23][24]. Quantum resistance devices based on graphene have been realized on graphene grown on silicon carbide wafer [20][21][22][23][24][25][26].…”
mentioning
confidence: 99%